Superior visible light antimicrobial performance of facet engineered cobalt doped TiO2 mesocrystals in pathogenic bacterium and fungi - Ayat N. El-Shazly (Nature Portfolio, 2021)
Abstract Pristine and Co-doped TiO2 mesocrystals have been synthesized via a simple sol–gel method and their antimicrobial activity has been investigated. The antimicrobial performance was evaluated in terms of zone of inhibition, minimum inhibitory concentration (MIC), antibiofilm activity, and effect of UV illumination in liquid media. The Co-doped TiO2 mesocrystals showed very promising MIC of 0.390 μg/mL and 0.781 μg/mL for P. mirabilis and P. mirabilis, respectively. Additionally, the material showed an MIC of 12.5 μg/mL against C. albicans, suggesting its use as antifungal agent. Upon the addition of 10.0 µg/mL of Co-doped TiO2 mesocrystals, the biofilm inhibition% reaches 84.43% for P. aeruginosa, 78.58% for P. mirabilis, and 77.81% for S. typhi, which can be ascribed to the created active oxygen species that decompose the tested microbial cells upon illumination. Thus the fabricated Co-doped TiO2 mesocrystals exhibit sufficient antimicrobial features under visible light, qualifying them for use as antimicrobial agents against pathogenic bacteria and fungi and subsequently inhibit their hazardous effects.